Seventh International Conference on Cryocrystals and Quantum Crystals Wroclaw, Poland, July 31st – August 5th, 2008 - Jeźowski, Andrzej; Kazimierski, Maciej (Физика низких температур, 2009)
This issue of the Fizika Nizkikh Temperatur contains
the Proceedings of the Seventh International Conference
on Cryocrystals and Quantum Crystals (CC-2008), held
in Wroclaw, Poland, July 31st to August 5th, 2008.